Pretreatment optimisation and kinetics of batch anaerobic digestion of liquidised OFMSW treated with NaOH: Models verification with experimental data - Bala R.; Gupta G.K.; Dasgupta B.V.; Mondal M.K. (My University, 2025)
The enormous generation of municipal solid waste (MSW) due to increased urbanization is causing threat to the environment. MSW is a mixed waste and it comprises of organic fraction as the key fraction called organic fraction of municipal solid waste (OFMSW) along with other fractions. The pretreatment of OFMSW is necessary step to increase the biogas yield. In the present work, NaOH hydrolysis of mechanically liquidised OFMSW was carried out to reduce its complexity and improve the biogas production. Furthermore, hydrolysis parameters were optimised by RSM model for NaOH pretreatment. Optimised conditions achieved from RSM analysis were 0.46 N NaOH loading, 72 h reaction time and 36.05 °C operating temperature. The RSM predicted values of response sCOD and VFA at optimum condition were in good agreement with experimental data signifying the model adequacy. The kinetic of batch anaerobic digestion of OFMSW treated with NaOH at different concentrations and optimised condition had been studied to see the suitability of first order model and modified Gompartz model. The experimental results obtained were best fitted using normalized root mean square error analysis. Biogas production after pretreatment at 0.1, 0.5, 0.9 N NaOH concentration and RSM optimised condition was 369.24, 435.24, 327.84 and 465.67 NL/kg VS, respectively. © 2019 Elsevier Ltd